2014
DOI: 10.4103/2277-9175.124650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection on stromal-derived factor-1/CXCR4 axis in bone marrow-derived mesenchymal stem cells

Abstract: Background:Recent studies have demonstrated that during chronic Helicobacter pylori (H. pylori) infection bone marrow-derived-mesenchymal stem cells (BMD-MSCs) migrate to the gastric tissue and could be also the origin of gastric adenocarcinoma. The chemokine CXCR4 through binding to its ligand stromal-derived factor (SDF-1) plays a crucial role in migration of inflammatory and stem cells. However, the possible effect of H. pylori infection on the SDF-1/CXCR4 axis has not yet been elucidated.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this study, OS was found to significantly correlate with CXCR4 expression, with the HR of 2.63 (95% CI: 1.69–4.09; P <0.0001), and a significant association was also detected between CXCR4 expression and tumor stage (odd ratio (OR): 0.52, 95% CI: 0.32–0.83; P = 0.007), depth of invasion (OR: 0.44, 95% CI: 0.27–0.73; P = 0.001), lymph node metastasis (OR: 2.30, 95% CI: 1.57–3.36; P <0.0001), and vascular invasion (OR: 0.72, 95% CI: 0.53–0.98; P = 0.04) (Han et al, 2014). Fakhari et al (2014) reported that Helicobacter pylori infection increased CXCL12 secretion by gastric epithelial cell line, upregulated CXCR4 expression in bone marrow-derived-mesenchymal stem cells, and enhanced their migration toward CXCL12 gradient. Findings by Oh et al (2012) indicate that hypoxia upregulates CXCR4 in gastric cancer cells in a HIF-1α-dependent manner and that upregulation of CXCR4 is involved in gastric cancer cell migration and invasion.…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
“…In this study, OS was found to significantly correlate with CXCR4 expression, with the HR of 2.63 (95% CI: 1.69–4.09; P <0.0001), and a significant association was also detected between CXCR4 expression and tumor stage (odd ratio (OR): 0.52, 95% CI: 0.32–0.83; P = 0.007), depth of invasion (OR: 0.44, 95% CI: 0.27–0.73; P = 0.001), lymph node metastasis (OR: 2.30, 95% CI: 1.57–3.36; P <0.0001), and vascular invasion (OR: 0.72, 95% CI: 0.53–0.98; P = 0.04) (Han et al, 2014). Fakhari et al (2014) reported that Helicobacter pylori infection increased CXCL12 secretion by gastric epithelial cell line, upregulated CXCR4 expression in bone marrow-derived-mesenchymal stem cells, and enhanced their migration toward CXCL12 gradient. Findings by Oh et al (2012) indicate that hypoxia upregulates CXCR4 in gastric cancer cells in a HIF-1α-dependent manner and that upregulation of CXCR4 is involved in gastric cancer cell migration and invasion.…”
Section: Role Of Cxcr4 In Cancermentioning
confidence: 99%
“…In most circumstances, the active recruitment of MSC commonly occurs ahead of GC initiation, especially in Hp-related carcinogenesis. Hp induced inflammation milieu is abundant in functional molecules such as TNF-a, TGF-b, CXCL12 and interferon g that conducive to MSC recruitment for their tissue healing functions (28,(87)(88)(89). Corresponding to this point, Ruan et al (27) labeled MSC with amino-modified FMNP that keep stable fluorescent signal and magnetic properties with 14 days to display out the early gastric cancer (EGC) area, not only being with the potential of imaging EGC, these MSC also could inhibit tumor growth markedly under alternating magnetic field irradiation.…”
Section: Target the Recruitment Course Of Msc And The Downstream Vicious Signalsmentioning
confidence: 99%
“…In most circumstances, the active recruitment of MSC commonly occurs ahead of GC initiation, especially in Hp-related carcinogenesis. Hp induced inflammation milieu is abundant in functional molecules such as TNF-α, TGF-β, CXCL12 and interferon γ that conducive to MSC recruitment for their tissue healing functions ( 28 , 87 89 ). Corresponding to this point, Ruan et al.…”
Section: The Prospects Of Msc In Targeted Therapymentioning
confidence: 99%
“…In order to prepare hBM-MSCs, bone marrow aspirate was harvested from the iliac crest of a normal donor who was negative for HIV, HBV and HCV laboratory tests, after informed consent was obtained. Then, hBM-MSCs were cultured and isolated as previously reported 26 . Mononuclear cells (MNC) were isolated by gradient centrifugation at 2,500 rpm for 30 minutes on Ficoll-Paque™ Plus (Amersham Pharmacia Biotech, Uppsala, Sweden).…”
Section: Isolation Culture and Characterization Of Hbm-mscsmentioning
confidence: 99%